PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS ENERGI DAN SUMBERDAYA MINERAL PROVINSI SULAWESI TENGAH - Hapsir, Mohamad (Katalogis, 2018)
The research means to determineÂ  and analyze simultaneous and partial influence of communication and motivation on the performance of officials in The Departemnt of Energy and Mineral Resources of Central Sulawesi Province. Sample consists of 87 officials in The Departement of Energy and Mineral Resources of Central Sulawesi regressions. Based on the results of t test and regression analysis, it is shown that communication and motivation positively and significantly influence the performance of officials in The Departement of Energy and Mineral Resources of Central Sulawesi 88.5% of officialsâ€™ performance influenced by communication and motivation, while 11.5% is influenced by other variables that are not studied.